Epicardial fat and coronary artery calcification in patients on long-term hemodialysis - Gauss, Soeren; Klinghammer, Lutz; Jahn, Daniela; Schuhbaeck, Annika; Achenbach, Stephan; Marwan, Mohamed (Journal of Computer Assisted Tomography, 2014)
Introduction: Recent studies have shown a significant correlation between increased epicardial fat volume (EFV) andmortality, coronary artery disease events, andmeasures of coronary atherosclerotic burden, for example, coronary calcium. Patients with chronic kidney disease on hemodialysis have an increased prevalence of coronary atherosclerosis and coronary calcium. The mechanisms underlying both may differ from patients with normal kidney function. Only limited data are available on the relationship between epicardial fat and coronary calcium in these patients.
CRIS-Team Scopus Importer:2023-03-08
Keywords: Cardiac CT; Coronary artery calcification; Dialysis; Epicardial fat